Clash of Realities 2015/16 : On the Art, Technology and Theory of Digital Games. Proceedings of the 6th and 7th Conference. (Bild und Bit. Studien zur digitalen Medienkultur., 2017)
Digital games as transmedia works of art - Games as social environments - The aesthetics of play - Digital games in pedagogy - Cineludic aesthetics - Ethics in games - these were some of the important and fascinating topics addressed during the internatio.